The Cambridge Kant lexicon - Wuerth, Julian (Cambridge University Press, 2021)
Immanuel Kant is widely recognized as one of the most important Western philosophers since Aristotle. His thought has had, and continues to have, a profound effect on every branch of philosophy, including ethics, metaphysics, epistemology, aesthetics, political philosophy, and philosophy of religion. This Lexicon contains detailed and original entries by 130 leading Kant scholars, covering Kant's most important concepts as well as each of his writings. Part I covers Kant's notoriously difficult philosophical concepts, providing entries on these individual 'trees' of Kant's philosophical system. Part II, by contrast, provides an overview of the 'forest' of Kant's philosophy, with entries on each of his published works and on each of his sets of lectures and personal reflections. This part is arranged chronologically, revealing not only the broad sweep of Kant's thought but also its development over time. Professors, graduate students, and undergraduates will value this landmark volume.
Title from publisher's bibliographic system (viewed on 26 Feb 2021)
Keywords: Kant, Immanuel -- 1724-1804 -- Encyclopedias; Wörterbuch; Kant, Immanuel